Web-Based Employee Leave Information System Design Using the Waterfall Method at the Deli Serdang District Agricultural Office - Risky Ananta Pradana; Muhammad Nabhan Akbar Marpaung (CV. Multimedia Teknologi Kreatif, 2026)
This study aims to address issues in employee leave data management at the Deli Serdang District Agricultural Office, where leave records were previously processed manually using separate documents, resulting in data duplication, inaccuracies, and delays in preparing reports. To solve this problem, a web-based Employee Leave Record Management System was developed using the Waterfall model through stages of requirements analysis, system design, implementation, testing, and maintenance. System evaluation was conducted using Black-Box testing to verify functional performance. The system supports structured recording of employee leave information, employee profile data such as position and department, and provides real-time reporting features to support administrative decision-making. The application was developed using the CodeIgniter-based MVC architecture and MySQL database, which enhances data accuracy, information accessibility, and administrative efficiency. The results demonstrate that the system successfully minimizes recording errors and improves the effectiveness of leave data management. Future development opportunities include integrating automated online leave request and approval workflows, mobile access features, and notification services to maximize usability and system automation.